Foreign -oriented feedback (KP) and (KR) and their impact on the development of precision strikes were the front and rear roller table for the national team players ( slow learners) - Mahdi, Rafid (Journal of Physical Education, 2014)
The research aims to identify the foreign - oriented feedback Tateraltgveh (KP) and (KR) the accuracy of the strikes in the development of the front and rear roller table of the national team players (slow learners). Turning researcher to theoretical studies which contained Detectives multiple on the subject of the search, has been used by researchers experimental approach to the suitability of the research problem , researcher selected sample discussed the way intentionalThey are national team players reel table (slow learners) totaling (7) players and a percentage of ( 100 %) of the original research. After the completion of the tests was to use statistical treatments appropriate to reach the results after the results were displayed and analyzed and discussed The researcher reached to the most important conclusions mentioned, as the most important recommendations was the need to pay attention to the feedback of State oriented (KP) and (KR) for their impact on the development of the accuracy of the strikes the front and rear reel table of national team players (slow learners)